Old wine in new bottles: The adaptive capacity of the hydraulic mission in Ecuador - Jeroen F. Warner; Jaime Hoogesteger; Juan Pablo Hidalgo (Water Alternatives, 2017)
Despite a widely embraced ecological turn and strident critique of megastructures in the 1990s, construction of large infrastructure has been reignited worldwide. While Integrated Water Resources Management (IWRM) and River Basin Management (RBM) have at least discursively held sway as the dominant paradigm in water management since the late 1990s, we argue that the 'hydraulic mission' never really went away and has in some places energetically re-emerged. The development discourse that justified many dams in the past is now supplemented by a new set of appealing justifiers. With the help of the case of Ecuador we show that the hegemonic project of the hydraulic mission has a great discursive adaptive capacity and a new set of allies. The rise of the BRICS (especially China), South-South cooperation and private investors provides non-traditional sources of funding, making the construction of hydraulic infrastructure less dependent on Western conditionalities. The resulting governance picture highlights the disconnect between the still widely embraced policy discourse of IWRM/RBM and the drivers and practices of the hydraulic mission; questioning what value international calls for 'good water governance' have in the midst of new discourses, broader transnational political projects and the powerful dam-building alliances that underlie them.